2018
DOI: 10.5603/fm.a2017.0100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valproic acid administration during pregnancy on postnatal development of cerebellar cortex and the possible protective role of folic acid

Abstract: The present study confirmed the protective role of folic acid against the cerebellar neurotoxic effects of VPA prenatal exposure. It is recommended that folic acid supplements should be given to every epileptic pregnant mother treated with VPA. (Folia Morphol 2018; 77, 2: 201-209).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
6
20
0
Order By: Relevance
“…In folate‐deficient models, FA supplementation partially reverses zebrafish neural tube 28 and rat brain defects 26 . Additionally, FA protects against VPA‐induced neural tube and brain defects in mice 25 and rats 39 . Together these reports emphasize the important function of FA for normal neurodevelopment.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In folate‐deficient models, FA supplementation partially reverses zebrafish neural tube 28 and rat brain defects 26 . Additionally, FA protects against VPA‐induced neural tube and brain defects in mice 25 and rats 39 . Together these reports emphasize the important function of FA for normal neurodevelopment.…”
Section: Discussionmentioning
confidence: 84%
“…26 Additionally, FA protects against VPA-induced neural tube and brain defects in mice 25 and rats. 39 Together these reports emphasize the important function of FA for normal neurodevelopment. Concordantly, we showed that FA supplementation protects against VPA-induced reduced midbrain size and hindbrain midline gap defects.…”
Section: F I G U R Ementioning
confidence: 89%
“…Therefore, if the epigenetic diet is a promising avenue for migraine treatment, studies on diets fortified with VPA should be undertaken. Notably, VPA has teratogenic potential and folate is speculated to act protectively against the side effects of VPA, although some results are contradictory [120,121,122].…”
Section: Discussionmentioning
confidence: 99%
“…Blocking DHFR function by administration of the folate analogue and DHFR antagonist methotrexate (MTX) leads to neurotoxic effects in the cerebellum of newborn rats [54] as well as to the degeneration of PCs in guinea pigs, which could be rescued by application of the tetrahydrofolate derivative leucovorin [55]. This rescue effect of folate is also apparent in newborn rats, in which PC atrophy and cerebellar degenerative changes induced by treatment with valproic acid in the mothers could be markedly reduced by an additional treatment with folic acid [56]. Conceivably, an impaired DHFR function may contribute to impaired cerebellar function.…”
Section: Discussionmentioning
confidence: 99%